From Informal Settlers to Homeowners: Community Organizing as a Process and Strategy for Empowerment - Calamba, Septrin John (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2019)
This paper examines the use of community organizing as an approach to community development in the context of TCVHOAI (Tomas Cabili Village Homeowners Association). Two main reasons are addressed for this sociological investigation 1) the land was privately owned that confronts eviction of the informal settlers 2) a coastal community in between two huge oil depots vulnerable to disasters. Utilizing community organizing as a tool for community empowerment in TCVHOAI, this paper argues that the strategic factors of empowerment such as processes, networks and partnerships, leadership, local organizational capacity, and challenges and outcomes are necessary for transformation of a community. This paper suggests that empowerment must be the ultimate goal of any community development project. Drawing from in-depth interviews with community organizers, government and non-government officials, members of the community, this paper supports that community organizing helps to achieve an empowered community with visible improvements in housing ownership, socio-economic conditions, access to basic social services, community participation, and other meaningful impacts in the lives of the people in the community.